RESEARCH-BASED REFLECTIONS ABOUT CHARACTER EDUCATION: MYTHS, CHALLENGES AND INTERNATIONAL PERSPECTIVES - Fernandezs, Manuels (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
At present, youngsters’ character and virtue education issues are widely discussed in Latvia and in English-speaking academic environment. Given the existing criticism of these concepts, the research question was: what are the main misunderstandings about the nature of character and virtue education? After clarifying the neo-Aristotelian understanding of these concepts, recent research in the field of character education and virtues is presented for deconstructing some of the myths related to it, due to conceptual, historical, moral and political misunderstandings (Kristjánsson, 2013). Real problems (historical, methodological and practical) faced by character education programs in mainstream schools are addressed. The importance of giving personal significance to eudaimonia for promoting character and virtue education at school is discussed.